Gas Price Policy Analysis for Fertilizer Industries in Indonesia Based on Netback from Final Product - Erwan Hermawan; Widodo Wahyu Purwanto (JURNAL SOSIAL HUMANIORA (JSH), 2020)
The industrial sector has an important role in the Indonesian economy. The problem facing the fertilizer industry is the price of gas as a raw material that tends to be expensive for the lower prices of crude oil since 2016. To overcome this problem the government issued Presidential Regulation No. 40/2016 on setting gas prices for the fertilizer industry but this regulation only sets floor gas prices at USD 6/MMBTU to secure revenues of gas producers. Meanwhile, the current sale gas contract for fertilizer applies an escalation. The objectives of this study are to evaluate the netback value of each fertilizer plant and assess the current gas price policy. The netback value is calculated based on the long-run marginal cost of urea production. The result shows that PKT 04 and PKT 05, Pusri 1B, 2B, 3, and 4, PKC 1A and 1B, and PKG have lower netback value than gas price contract, except for PKT plant based on average has the highest netback value, because they use pricing mechanism that linked to oil and product price. From this calculation the current gas price policy needs to be adjusted to keep the fertilizer industry profitably.